2011
DOI: 10.1007/bf03262782
|View full text |Cite
|
Sign up to set email alerts
|

Laser restorative dentistry in children and adolescents

Abstract: The laser erbium technology represents a safe device to effectively and selectively remove carious tissues from decayed teeth. For children, all the recognized advantages of this technique play a decisive role in the successful day-to-day treatment of dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 42 publications
3
43
0
6
Order By: Relevance
“…61 The ability of hard tissue lasers to reduce or eliminate vibrations, the audible whine of drills, microfractures, and some of the discomfort that many patients fear and commonly associate with high-speed handpieces has been described as impressive. 62 High caries prevalence in occlusal pits and fissures has warranted the search for novel prevention methods. The capability of lasers to modify enamel surface properties has promised a new type of caries prevention therapy.…”
Section: Lasers For Minimally Invasive Preparation and Caries Preventionmentioning
confidence: 99%
“…61 The ability of hard tissue lasers to reduce or eliminate vibrations, the audible whine of drills, microfractures, and some of the discomfort that many patients fear and commonly associate with high-speed handpieces has been described as impressive. 62 High caries prevalence in occlusal pits and fissures has warranted the search for novel prevention methods. The capability of lasers to modify enamel surface properties has promised a new type of caries prevention therapy.…”
Section: Lasers For Minimally Invasive Preparation and Caries Preventionmentioning
confidence: 99%
“…It has been reported that using an erbium: yttrium aluminium garnet (Er:YAG) laser for cavity preparation produces minimal vibration and noise, minimal or no need for local analgesia, reduction of stress, and minimal removal of sound tooth structure, as well as providing a better surface for adhesive restorative materials [68]. Therefore, the use of lasers in pediatric dentistry has increased recently [9–11]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that laser fluorescence (LF) can enhance the accuracy and speed of clinical detection of caries. 16,17 LF at a wavelength of 655 nm (nonablative with red light) can be used as an adjunct for disclosing occlusal caries in primary and permanent teeth and due to its high reliability, predictability and reproducibility, it decreases diagnostic errors. 17,18 DIAGNOdent is a commercial product using LF technology.…”
Section: Hard Tissue Applications Of Lasermentioning
confidence: 99%
“…16,17 LF at a wavelength of 655 nm (nonablative with red light) can be used as an adjunct for disclosing occlusal caries in primary and permanent teeth and due to its high reliability, predictability and reproducibility, it decreases diagnostic errors. 17,18 DIAGNOdent is a commercial product using LF technology. An in vitro study demonstrated its superior efficacy for disclosing occlusal dentin caries in primary teeth in comparison to visual inspection, probing and radiography.…”
Section: Hard Tissue Applications Of Lasermentioning
confidence: 99%